THE INFLUENCE OF DIGITAL MEDIA ON LEARNING OUTCOMES OF SCIENCE MATERIAL EVALUATION IN ELEMENTARY SCHOOLS - Cut Oktanalisa; Yulia Richi; Lisnawati Lisnawati; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Technological advances have brought significant changes in the world of education, including in the teaching of Natural Sciences (IPA) in elementary schools. This study aims to analyze the effect of the use of digital media on the evaluation results of Natural Sciences (IPA) learning in elementary schools (SD). Digital media, such as interactive learning applications, animated videos, and online quizzes, are increasingly being used to support the learning process. This study used a quantitative method with a quasi-experimental design, involving two groups of fifth grade elementary school students, namely the control group with conventional methods and the experimental group using digital media. Data were obtained through pretests and posttests to measure the increase in understanding of science concepts in both groups. The results showed that students who learned using digital media experienced a significant increase in evaluation results compared to students who used traditional learning methods. In addition, digital media has been shown to increase student interest in learning and involvement in science learning. This study concludes that the integration of digital media in science learning can be an effective strategy to improve learning outcomes in elementary schools.